Heterogeneity and developmental dynamics of LYVE-1 perivascular macrophages distribution in the mouse brain. Issue 10 (October 2022) - Karam, Marie; Janbon, Hadrien; Malkinson, Guy; Brunet, Isabelle
Brain perivascular macrophages (PVMs) are border-associated macrophages situated along blood vessels in the Virchow-Robin space and are thus found at a unique anatomical position between the endothelium and the parenchyma. Owing to their location and phagocytic capabilities, PVMs are regarded as important components that regulate various aspects of brain physiology in health and pathophysiological states. Here, we used LYVE-1 to identify PVMs in the mouse brain using brain-tissue sections and cleared whole-brains to learn about how they are distributed within the brain and across different developmental postnatal stages. We find that LYVE-1 + PVMs associate with the vasculature in different patterns and proportions depending on vessel diameter or arterio-venous differentiation. LYVE-1 + PVMs relate to blood vessels in a brain-region-dependent manner. We show that their postnatal distribution is developmentally dynamic and peaks at P10-P20 depending on the brain region. We further demonstrate that their density is reduced in the APP/PS1 mouse model of Alzheimer's Disease proportionally to beta-amyloid deposits. In conclusion, our results reveal unexpected heterogeneity and dynamics of LYVE-1 + PVMs, with selective coverage of brain vasculature, compatible with potential unexplored roles for this population of PVMs in postnatal development, and in regulating brain functions in steady-state and disease conditions.